2023
DOI: 10.1039/d2cp01994a
|View full text |Cite
|
Sign up to set email alerts
|

The origin of isomerization of aniline revealed by high kinetic energy ion mobility spectrometry (HiKE-IMS)

Abstract: Three ion mobility peaks of 4-fluoroaniline, including the para-protonated and molecular ion species, when measured with a high-kinetic energy ion mobility spectrometer and peak abundances depend only on the ionization settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…Sophisticated mobility modeling software would be needed to fully characterize differences due to substituent position. 67 As previously reported for the fluoroanilines measured in N 2 , 66 4-chloroaniline and 4-bromoaniline also have a third peak which elutes between the 3-substituted peak 1 and the 2-substituted peak 2. The change in mobility for peak 3 also appears parallel to the respective peak 1 which results in nearly the same alpha function.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Sophisticated mobility modeling software would be needed to fully characterize differences due to substituent position. 67 As previously reported for the fluoroanilines measured in N 2 , 66 4-chloroaniline and 4-bromoaniline also have a third peak which elutes between the 3-substituted peak 1 and the 2-substituted peak 2. The change in mobility for peak 3 also appears parallel to the respective peak 1 which results in nearly the same alpha function.…”
Section: Resultssupporting
confidence: 66%
“…The origin and ionization of all three peaks have been examined in a previous publication for aniline and n -fluoroanilines and the other halogenated anilines display similar behavior with regard to the number of peaks. 66 The reduced electric field in the reaction region was chosen because that is the value where peaks 1 and 2 have nearly the same intensities which allow for the characterization of both peaks as the reduced electric field in the drift region is changed. All ion mobilities, drift times, experimental parameters, CCS values, and alpha values for both peaks at all reduced electric field strengths are included in the ESI †…”
Section: Resultsmentioning
confidence: 99%
“…They are exceptionally rare isomers of aniline (<10 −15 % [22]). However, the imine forms are often used as intermediate structures to understand the mechanism of various chemical reactions and to confirm the product formation [19,[22][23][24][25][26]. The resonance energy (aromatic stability > 30 kcal mol −1 [27]), being considerably higher than the energy of prototropy in aniline, can only explain the change of isomeric preference when going from simple aliphatic to aromatic enamine-imine tautomeric systems.…”
Section: Equilibriamentioning
confidence: 99%
“…30−34 Among the four possible protonation sites, the para-protonated and aminoprotonated forms have been considered to be the two most stable tautomers of protonated aniline. 34 Despite extensive research efforts dedicated to this subject, the mass spectrometry community has yet to devise a reliable method for predicting the population ratio of protomers within an ensemble of gas-phase ions. 30,31,35−38 Evidently, these ion ratios are far from being intrinsic; instead, they are highly dependent on the conditions of ionization and the instrumental manipulations following ionization.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Moreover, for more than a decade, it has been recognized that even simple monofunctional compounds such as aniline can exist in various protonated forms. Among the four possible protonation sites, the para-protonated and amino-protonated forms have been considered to be the two most stable tautomers of protonated aniline . Despite extensive research efforts dedicated to this subject, the mass spectrometry community has yet to devise a reliable method for predicting the population ratio of protomers within an ensemble of gas-phase ions. ,, Evidently, these ion ratios are far from being intrinsic; instead, they are highly dependent on the conditions of ionization and the instrumental manipulations following ionization. , We have previously demonstrated that the ratio of the para- and amino-protonated ion peaks of aniline was dependent on the post-ESI source conditions such as sampling-cone voltage, which can have a major impact on observed tautomer distributions, However, there is significant debate about the mechanisms involved in the process of transformation.…”
Section: Introductionmentioning
confidence: 99%